PELATIHAN PLYOMETRIC BROAD JUMP LEBIH MENINGKATKAN KEMAMPUAN LOMPAT JAUH DARI PADA PELATIHAN PLYOMETRIC BOX JUMP - S. P. Dedy Darma Yasa; K. Tirtayasa; I P. Gede Adiatmika; Luh Made Indah Sri Handari Adiputra; Made Muliarta; Ida Bagus Ngurah (Program Studi Magister Fisiologi Keolahragaan, Fakultas Kedokteran, Universitas Udayana, 2017)
Long jump ability is part of athletic event, which was based on power ability. Meanwhile power was influenced by the type of training. Among some training types there are plyometric broad jump training and plyometric box jump training.The purpose of this research is to find out which one is more effective to increase the long jump ability between plyometric broad jump training and plyometric box jump training. Pretest – Posttest two group designs was used in this study. Samples of the study were taken from male students of Primary Secondary School or Sekolah Menengah Pertama (SMP) PGRI 2 Denpasar. Students were randomly divided into two groups (group 1 and group 2) each consist of 12 subjects proportionally. Group 1 was trained plyometric box jump and group 2 was trained plyometric broad jump respectively. The durationof training was 6 weeks and the frequency was three time a week. The test of long jump was carried out before and after 6 weeks training. These pre and post result of distance of long jump were compared each other. The result and statistical t-test analysis are as follows. Mean distance of long jump before training of group 1(344.25 cm) and group 2 (355.75 cm) was not significantly difference (p > 0.05). Meanwhile result after training of group 1 (mean 374.75 cm, increasing jump 30.50 cm) and group 2 (mean 397.33 cm, increasing jump 41.58 cm), were also significantly difference (p < 0.05). This study conclude that plyometric broad jump training more increasing the ability to long jump than plyometric box jump training among male students SMP PGRI 2 Denpasar. The value of mean difference was 11.08 cm. It is recommended to coaches and sport teachers can choose this broad jump training method to increase the ability of long jump of primary high school students.